Ecological niche differentiation among Aztec fruit-eating bat subspecies (Chiroptera: Phyllostomidae) in Mesoamerica - Hernández-Chávez, Iván; Guevara, Lázaro; Arroyo-Cabrales, Joaquín; León-Paniagua, Livia (THERYA, 2023)
Artibeus aztecus is a Mesoamerican montane bat with three currently recognized, allopatric subspecies. No study has evaluated the phylogenetic status of the subspecies. However, through an analysis of its ecological niche and its geographic distribution, here we analyze whether there is differentiation of the climatic requirements for each subspecies, assessing whether niche evolution is a potential factor in subspecies differentiation. We assayed ecological niche models for each subspecies, analyzed the response curves for the most important climatic variables of each model, and generated the potential distribution model for each subspecies. We assayed a background similarity test between the subspecies to determine how similar their niches were. We found differences in climatic requirements for the three allopatric subspecies and the most important variables and their response curves. Potential distribution models concur with Mesoamerican highlands and highlight the lowlands of the isthmus of Tehuantepec and the Nicaraguan depression as possible geographic barriers. Differences found between ecological niches for each subspecies contrast with previous findings for the species and other phyllostomid bats. Niche conservatism may have caused geographic isolation in the past, and differences in environmental requirements may have appeared later. Molecular and morphological analyses are necessary to clarify the taxonomic status of these populations and the evolutionary processes involved in their diversification.